2015
DOI: 10.1002/ajh.24075
|View full text |Cite
|
Sign up to set email alerts
|

KITD816V and JAK2V617F mutations are seen recurrently in hypereosinophilia of unknown significance

Abstract: Myeloproliferative neoplasms with eosinophilia are commonly characterized by a normal karyotype and remain poorly defined at the molecular level. We therefore investigated 426 samples from patients with hypereosinophilia of unknown significance initially referred for screening of the FIP1L1-PDGFRA (FP) fusion gene also for KIT D816V and JAK2 V617F mutations. Overall, 86 (20%) patients tested positive: FP1 in 55 (12%), KIT D816V1 in 14 (3%), and JAK2 V617F1 in 17 (4%) patients, respectively. To gain better insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 27 publications
1
50
0
3
Order By: Relevance
“…KIT M541L mutations were recently reported in four of five chronic eosinophilic leukemia, not otherwise specified patients who did not have PDGFRA/B lesions but responded to tyrosine kinase inhibitor treatment. 18 Schwaab and colleagues 19 reported KIT 816 V mutations in 3% (14 patients) and JAK2 V617F mutations in 4% (17 patients) of patients who presented with hypereosinophilia of unknown significance. Notably, with the mutation information and upon review of the slides, the authors reclassified the cases with KIT D816V as systemic mastocytosis with eosinophilia (systemic mastocytosis-eo) and cases with JAK2 V617F mutation as myeloproliferative neoplasm with eosinophilia (myeloproliferative neoplasm-eo).…”
Section: Discussionmentioning
confidence: 99%
“…KIT M541L mutations were recently reported in four of five chronic eosinophilic leukemia, not otherwise specified patients who did not have PDGFRA/B lesions but responded to tyrosine kinase inhibitor treatment. 18 Schwaab and colleagues 19 reported KIT 816 V mutations in 3% (14 patients) and JAK2 V617F mutations in 4% (17 patients) of patients who presented with hypereosinophilia of unknown significance. Notably, with the mutation information and upon review of the slides, the authors reclassified the cases with KIT D816V as systemic mastocytosis with eosinophilia (systemic mastocytosis-eo) and cases with JAK2 V617F mutation as myeloproliferative neoplasm with eosinophilia (myeloproliferative neoplasm-eo).…”
Section: Discussionmentioning
confidence: 99%
“…In the past, clonality had been mainly determined by chromosomal analysis or mutations well known to occur in MPNs, such as JAK2, MPL, CALR, or KIT. However, it has been shown that these mutations are extremely uncommon in CEL, NOS [80,81]. In recent years, using NGS technology, somatic mutations associated with myeloid neoplasms have been detected in 25-30% of patients who have a normal karyotype and no increase in blasts and who would otherwise be considered to be idiopathic DOI: 10.1159/000489341 HES.…”
Section: Cel Nos and Idiopathic Hesmentioning
confidence: 99%
“…Most commonly, translocations or other genomic rearrangements generate TK fusion genes, e.g., FIP1L1-PDGFRA , ETV6-PDGFRB , ZMYM2-FGFR1 , PCM1-JAK2 , and many others [2], but some cases test positive for activating TK point mutations such as KIT D816V or JAK2 V617F [4]. Identifying driver fusion genes is critical for clinical management, e.g., patients with PDGFRA or PDGFRB rearrangements have excellent responses to imatinib, with most cases achieving sustained hematological and molecular remission [5,6,7].…”
Section: Figmentioning
confidence: 99%